Penerapan Alat Evaluasi Matching Card PBL-CIRC Mengukur Berpikir Kritis Siswa Kelas V Materi Pidato - Azzahra, Meuthia; Purwati, Panca Dewi (YASIN, 2025)
This study originates from the problem of limited authentic assessment instruments that specifically measure elementary students’ critical thinking skills, particularly in speech text learning. It aims to develop, implement, and validate a matching card evaluation tool based on Problem-Based Learning (PBL) and Cooperative Integrated Reading and Composition (CIRC) to assess fifth-grade students’ critical thinking abilities. A mixed-methods approach with a concurrent embedded design was employed, involving 28 students. Quantitative data were obtained from matching card results, while qualitative data were collected through classroom observations, questionnaires, and interviews. The findings show that the integration of PBL and CIRC increases students’ engagement in analyzing text structure, identifying main ideas, and evaluating the interrelationships among text elements. The matching card instrument proved effective in measuring critical thinking indicators, as evidenced by an average score of 78.2 and a classical mastery level of 82.1%. Qualitatively, 85.7% of students stated that the instrument helped improve their understanding, accuracy, and confidence during assessment. These results lead to the conclusion that matching cards provide valid evidence of students’ analytical, interpretive, and relational thinking processes, and contribute to strengthening literacy-based pedagogy through authentic assessment aligned with higher-order thinking skills. The implications of this study include opportunities for broader implementation, the need for long-term evaluation of critical thinking development, and the potential integration of the instrument into digital platforms, alongside recommendations to refine the level of card complexity and test the instrument in more diverse student populations.